Регіональний аспект формування потенціалу фінансової безпеки аграрних підприємств. - Пристемський, О.С.; Трусова, Наталя Вікторівна; Trusova, Natalia (Мелітополь, ТДАТУ, 2021)
UKR У статті розглядається потенціал фінансової безпеки, що формує систему фінансового захисту життєво важливих інтересів суб’єктів аграрного сектору. Доведено, що під тиском зовнішнього середовища інструменти впливу та фінансового механізму можуть змінюватися. Виокремлено пріоритет фінансової підт римки сільського господарства України за показниками інтенсивності та ефективності використання фінансо вих ресурсів. Запропоновано комплексний показник потенціалу фінансової безпеки. Розроблена модель стабільно го рівня потенціалу спроможності фінансового забезпечення на основі чистого прибутку. \\\\\\\\\\\\\\\ ENG The article deals with the potential of financial security, which forms the system of financial protection of vital interests of subjects of the agrarian sector through the guarantee of food security in the long-term, at the expense of reproductive level of financial support. It is proved that under the pressure of the external environment, leverage and financial mechanism tools that trigger the potential of financial security of agriculture can change, risk manifestation and economic depression of enterprises continue or stop. The importance of forming the aggregate value of the poten tial of financial security in the region is due to its component, which is capable of performing actions to mobilize the real and hidden possibilities of financial resources in a limited time period, to overcome the threats to a safe environ ment for the functioning of agrarian enterprises. The priority of financial support of agriculture of Ukraine according to indicators of intensity and efficiency of use of financial resources is singled out. A comprehensive indicator of poten tial of financial security is proposed. A differentiated approach to the clustering of the k-medium method – indicators of the use of financial resources as interdependence of the factors of the formation of the aggregate magnitude of the po tential of financial security of agrarian enterprises in the regions of Ukraine was used. With the help of inductive sys tem analysis, a model of a stable level of potential of financial security capacity based on net profit has been developed. The model is adequate, its statistical quality, significance and reliability are sufficient for forming the forecast level of potential of financial security of agrarian enterprises of the region. The developed methodology is based on the compo nents of the protection of financial system of economic entities in the conditions of the restrictions of the choice of al ternative sources of formation and distribution of financial resources, as well as the likelihood of their use.
Regional aspect of formation of potential of financial security of agricultural enterprises.
Keywords: потенціал; фінансова безпека; фінансові ресурси; фінансова підтримка; фінанси сільського господарства; аграрні підприємства; potential; financial security; financial support; agrarian enter prises; financial resources; agricultural finance